POTENTIAL OF ANGIOTENSIN-CONVERTING ENZYME INHIBITORS IN THE TREATMENT OF PATIENTS WITH ARTERIAL HYPERTENSION AND CORONARY HEART DISEASE - A. G. Evdokimova; V. V. Evdokimov (Кардиоваскулярная терапия и профилактика)
For the last 30 years, angiotensin-converting enzyme (ACE) inhibitors have been playing a key role in the management of arterial hypertension (AH) and related cardiovascular disease. This review discusses the mechanisms of action and organo-protective effects of ACE inhibitors. Enalapril is the most extensively studied and widely used in the international clinical practice ACE inhibitor. The authors analyse the results of the studies on enalapril therapy in AH, coronary heart disease (CHD), chronic heart failure, metabolic syndrome, and postmenopause. It has been demonstrated that the combination antihypertensive therapy with a β-adrenoblocker nebivolol, enalapril, and hydrochlorothiazide (such as Berlipril® Plus) is safe and effective in patients with AH and CHD.